HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI PEMASARAN SMK N 1 MERANGIN - Melpa Sigalingging; Ahde Fitri; Sugeng Riyadi (Mat-Edukasia, 2021)
This research is a quantitative correlational study that describes the relationship between two variables, namely learning motivation and learning outcomes. The population of this study were 44 students of class XI Marketing SMK N 1 Merangin. The sampling technique used total sampling technique. Data were collected by distributing questionnaires for learning motivation and documentation to obtain data on the score of mathematics learning outcomes. The questionnaire was distributed online because the learning process was still being carried out online with a total of 10 items. The results of the research data analysis obtained rcount for the learning motivation variable (X) with mathematics learning outcomes (Y) of 2.419 and the score of rtabel = 0.297. So, rcount > rtabel or 0.477> 0.297, namely Ho is rejected and H1 is accepted, which means there is a relationship. For the level of significance using the Z test with the results of Zhitung > Ztabel or 15.862 > 0.4429, there is a significant relationship. The conclusion of this study is that there is a significant relationship between learning motivation and mathematics learning outcomes of class XI Marketing students of SMK N 1 Merangin in the 2019/2020 academic year